ChemInform Abstract: Efficient Hydroarylation and Hydroalkenylation of Vinylarenes by Broensted Acid Catalysis. Issue 52 (6th December 2016) - Liu, Muwen; Zhang, Jinlong; Zhou, Hui; Yang, Huameng; Xia, Chungu; Jiang, Gaoxi
Abstract: Broensted acid Tf2 NH catalyzes Friedel—Crafts type head‐to‐tail hydroalkenylation and hydroarylation of vinylarenes [(I), (III), (V), and (VII)] under mild reaction conditions providing a readily scalable, metal‐free, and practical access to bioactive trans‐1, 3‐diaryl‐1‐butenes [(II), (IV), and (IX)] and cyclic analogues [(VI) and (VIII)] and 1, 1‐diarylalkanes (XI), resp., in high regioselectivity.